2016
DOI: 10.4194/1303-2712-v16_1_19
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was carried out by the streams of Tunceli province (Turkey) between June 2008 and May 2009 to determine Mollusca fauna. Samples were taken at 20 stations, seasonally. Mollusca fauna of the streams of Tunceli was represented by three species of Prosobranchia (Bithynia pseudemmericia, Bithynia tentaculata, Anadoludamnicola gloeri), four species of Pulmonata (Galba truncatula, Radix labiata, Physella acuta, Acroloxus lacustris), and two species of Bivalvia (Pisidium casertanum, Pisidium lilljeborgii). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…In the present study, all the determined species of Gastropoda are commonly live clean water; they cannot survive in heavily polluted waters. Koşal Şahin and Zeybek (2016) reported that Acroloxus lacustris was showed positive correlation with DO values in Tunceli streams. Theodoxus species commonly lives in running waters of turbulent waters includes taxa living in springs, rivers, lakes and even in low-salinity waters and sometimes on the vegetation (Roth, 1987;Yıldırım, 2004;Yıldırım et al, 2006).…”
Section: Resultsmentioning
confidence: 97%
“…In the present study, all the determined species of Gastropoda are commonly live clean water; they cannot survive in heavily polluted waters. Koşal Şahin and Zeybek (2016) reported that Acroloxus lacustris was showed positive correlation with DO values in Tunceli streams. Theodoxus species commonly lives in running waters of turbulent waters includes taxa living in springs, rivers, lakes and even in low-salinity waters and sometimes on the vegetation (Roth, 1987;Yıldırım, 2004;Yıldırım et al, 2006).…”
Section: Resultsmentioning
confidence: 97%
“…Biyolojik izleme programlarında en çok kullanılan ve SÇD kapsamında bir kalite unsuru olan taban büyük omurgasızları su kütlesi hakkında kapsamlı bir değerlendirme imkânı sunmaktadır (Karr, 1999;Kenney, Sutton-Grier, Smith, ve Gresens, 2009;Kazancı vd., 2010). Taban omurgasızları içinde önemli bir yeri olan tatlısu molluskları hakkında ülkemizde yapılan ilk çalışmalar Roth (1839) ile başlamış, müteakiben yerli ve yabancı çok sayıda bilimsel çalışmayla (Schütt, 1964;Schütt ve Bilgin, 1970;Bilgin, 1980;Schütt ve Şeşen, 1993;Yıldırım, 1999;Ustaoğlu, Balık ve Özbek, 2001Öktener, 2004;Yıldırım vd., 2006;Kebapçı ve Yıldırım, 2010;Kılıçaslan ve Özbek, 2010;Koşal-Şahin, Bahadır-Koca ve Yıldırım, 2012;Odabaşı ve Georgiev, 2014;Yıldırım, Kebapçı, Koca ve Yüce, 2015;Koşal-Şahin ve Zeybek, 2016;Gürlek, 2017;Gürlek, Koşal-Şahin, Dökümcü ve Yıldırım, 2019;Gözler ve Baytaşoğlu, 2020;Tomilova vd., 2020;Odabaşı, Akay ve Koyuncuoğlu, 2020;Sands vd., 2020) hız kazanmıştır.…”
Section: Introductionunclassified
“…There are a few biological studies related to fish, trichoptera and mollusca fauna of the streams of this region such as: "the meat yield and chemical composition of Salmo trutta macrostigma caught in Munzur River" [9], the distribution of larval trichopteran assemblages [10] and mollusca fauna of the streams of Tunceli [11].…”
Section: Introductionmentioning
confidence: 99%